2006 International Conference on Computing &Amp; Informatics 2006
DOI: 10.1109/icoci.2006.5276513
|View full text |Cite
|
Sign up to set email alerts
|

The acceptance of e-Book readers among Malaysian children

Abstract: This paper describes a study on electronic book (eBook) among Malaysian children. The main purpose of this study is to investigate the Malaysian children acceptance of three types of eBook readers (i.e. Plus, Comic, and Spiral). The acceptance study is based on users' perceptions on ease of use and usefulness of the three readers. As a result, majority of respondents do not give clear distinction among the readers. Generally, all readers are useful and easy to use because very big majority of the respondents (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Recognizing its potential in academia, e-Book has been adopted in the education system in many countries [1][2].To date, more than 20 countries including Malaysia have utilized e-Book in their education system reaping positive effects from studentand teacher groups [3]. The e-Book project in Malaysia is spearheaded by the State of Terengganu with the distribution of e-Book to primary school childrenaged 10-12 years old.…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing its potential in academia, e-Book has been adopted in the education system in many countries [1][2].To date, more than 20 countries including Malaysia have utilized e-Book in their education system reaping positive effects from studentand teacher groups [3]. The e-Book project in Malaysia is spearheaded by the State of Terengganu with the distribution of e-Book to primary school childrenaged 10-12 years old.…”
Section: Introductionmentioning
confidence: 99%
“…Pupils' development can be closely and conveniently monitored, documented, categorized and accessed [13]. It is suggested that an IT support staff is required in each school to monitor all the e-books and to ensure the e-books function optimally.…”
Section: Recommendationsmentioning
confidence: 99%